NAVIGATING AMBIGUITY: COGNITIVE SEMANTICS OF POLYSEMOUS TITLES IN BREAKING BAD - kurnia idawati; Soepriyatna; Ariza Purnawati; Juliansyah (CALL, 2026)
This paper investigated how episode titles in Breaking Bad (2008–2013) carried multiple interconnected meanings that influenced narrative interpretation. By applying a cognitive semantics framework, it explored how polysemous titles activated semantic networks and invited dynamic reinterpretation as the story unfolded. Using qualitative content analysis, four episodes—Pilot (S1E1), Cancer Man (S1E4), Crazy Handful of Nothin’ (S1E6), and I See You (S3E8)—were examined for literal and metaphorical layers of meaning. Findings revealed that titles functioned simultaneously as direct references (e.g., medical diagnosis, poker bluff, hospital surveillance) and as metaphorical devices (e.g., Walt as “pilot” of his destiny, cancer as moral decay, bluff as illusion of power, surveillance as vulnerability). Cognitive semantics explained how audiences process these layered meanings: viewers initially interpreted titles literally, but as narrative contexts evolved, they re-accessed metaphorical dimensions through semantic network activation. These layered meanings enriched character arcs, foreshadowed conflicts, and amplified thematic resonance, particularly in the exploration of morality, identity, and consequence. By highlighting polysemy as both a linguistic and cognitive-semantic device, this research contributed to television studies and linguistic analysis, offering new insights into how ambiguity in language deepened storytelling and sustained audience engagement across disciplines.